Adaptive Control System Design Based On Lora SX1278 For Wireless Sensor Network Monitoring - Beni Satria (CERED Indonesia Institute, 2025)
Wireless sensor network-based monitoring systems have become essential for various industrial and environmental applications, particularly for monitoring conditions requiring wide coverage and low power consumption. LoRa SX1278 technology offers a long-range communication solution with high energy efficiency, but challenges remain regarding data stability, channel interference, and the need to adapt to changing environmental conditions. This study presents the design of a LoRa SX1278-based adaptive control system for wireless sensor network monitoring, focusing on improving transmission reliability and adaptive response to signal dynamics. This system integrates a LoRa SX1278 module, a microcontroller as the main controller, and an adaptive control algorithm that adjusts communication parameters in real time based on channel conditions. Tests were conducted using several distance scenarios and physical obstacles to evaluate system performance in terms of delay, packet loss, and signal stability. The test results show that the implementation of adaptive control can improve communication quality by more than 20% compared to static methods, while ensuring continuity of monitoring data under changing environmental conditions. The main contribution of this study lies in the integration of the adaptive algorithm with the LoRa SX1278 module, which can be used as a reference in the development of large-scale IoT systems in the future.